Fenomena Dakwah Online dan Offline Ustadz Abdus Somad di Pondok Pesantren Al-Amien Prenduan Sumenep Madura - Muhammad Munir (IAIN Salatiga, 2019)
This research was conducted to find out how the phenomenon of online propaganda that occurred among pesantren and the Madurese community, welcomed the arrival of Ustadz Abdus Somad, in facing the challenges of social media today. By using a qualitative research approach. The results of this study indicate that the views of the santri community and alumni of Al-Amien Prenduan Islamic boarding school on the phenomenon of online propaganda are three, namely: challenge from offline media, challenges from online media, internet as media propaganda. (a) The challenge of Offline Media is the challenge in the form of the order at the venue, such as the sound system, the audience, the presence of the audience, (b) The challenge of online media is that organizers must be able to arrange for online media to be noticed also because this really helps the virtual community to be able to watch when they are unable to attend the place of the event (c) the Internet as a propaganda media, this is one of the advantages of the internet in the realm of da’wah that is able to search for content, videos, and new things.